Analisis Strategi Distribusi Dan Penentuan Harga Produk Baru Untuk Meraih Loyalitas Pelanggan Di Pt Maxis Paragon Kota Gunungsitoli - Waruwu, Martin; Zebua, Emanuel; Gea , Nov Elhan; Telaumbanua, Eliagus (LPPM Universitas HKBP Nommensen, 2024)
Study This aim For know strategy marketing At PT. Maxis Paragon Gunungsitoli City And For know Strategy in distribution And determination price product For can reach Loyalty purchase at PT Maxis Paragon Gunungsitoli City . Type study This is study qualitative This use instrument study with guided on type research in _ use is form of interview instrument and observation amount informant on study This consists from 8 respondents . Based on results study that PT Maxis Paragon Gunungsitoli City own strategy in marketing that is with use segmentation market, targeting market And Differentiation And Position Market And in accordance with strategy in _ have , and in determine by ability And level education in _ have by employees. Strategy in marketing very determine in increase Distribution Product For can reach loyalty customer at PT Maxis Paragon Gunungsitoli City for less employees _ ability No give task or work , with exists training so they Can apply strategy marketing And increase Distribution product with exists training so Can know strategy And become something provisions in field marketing. At PT Maxis Paragon Gunungsitoli City walk with fluent And routine in enhancement Distribution For can reach loyalty customer very Good And No There is the obstacles that arise experience in company that